PENERAPAN MODEL INKUIRI TERSTRUKTUR BERBANTUAN LKPD UNTUK MENINGKATKAN AKTIVITAS DAN KOMPETENSI BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPA KLS VIII A SMPN 4 TANDUN ROKAN HULU - Zaenab, Nurul; Razak, Abdul; Anhar, Azwir (Kolaboratif, 2015)
This research was based on the poor state of students’ learning activities which results on the poor learning competence they had. The objectives of this research were to determine the process of  improvement of the  learn activities and competence of grade VIII A students of SMPN 4 Tandun, regarding their knowledge, attitude, and skills, through The Implementation of Stuctured  Inquiry Model by Using LKPD.This research was conducted in two cycles each cycle consists of planning, implementation, observation, and reflection which were started by doing the initial reflection before the first cycle. The subjects of this research were 22 grade VIII A students of SMPN 4 Tandun. The research suggested that there was an improvement in students’ activities and competence after the learning structured inquiry model by using LKPD was implemented.